The put-em-rights - Blyton, Enid (Award Publications Limited London, 2010)
The Put-Em-Rights by Enid Blyton is a charming children$1 (Bs story that follows a group of friends known as the "Put-Em-Rights." The children are dedicated to helping others resolve their problems and mend misunderstandings in their community. They take on various challenges, from solving disputes among neighbors to helping out in local events. Through their clever ideas and teamwork, they teach valuable lessons about kindness, friendship, and the importance of standing up for what is right. The story is filled with humor and heartwarming moments, showcasing the impact of compassion and cooperation.s